ChemInform Abstract: Synthesis and Evaluation of a Series of Piperidine‐2, 6‐dione‐piperazine (piperidine) Derivatives as Multireceptor Atypical Antipsychotics. Issue 11 (8th March 2013) - Chen, Yin; Xu, Xiangqing; Liu, Xin; Liu, Bi‐Feng; Zhang, Guisen
Abstract Compound (I) shows high affinity for dopamine D2 and D3, serotonin 5‐HT1A, 5‐HT2A, and 5‐HT2C receptors with a low affinity for the H1 receptor.